APPLICATION OF INTEGRAL EQUATION AND HYBRID TECHNIQUES TO THE PARALLEL COMPUTATION OF ELECTROMAGNETIC FIELDS IN A DISTRIBUTED MEMORY ENVIRONMENT - Jakobus, Ulrich (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper describes the parallelization of the method of moments and hybrid code FEKO for execution on massively parallel supercomputers with a distributed memory as well as on clusters of connected workstations. The parallel implementation of the different phases of the solution process, e.g. matrix fill, solution of the system of linear equations, and near- and far-field computation is discussed in detail. Several results for different applications are given and the achieved performance is presented